STRATEGIES TO INCREASE THE PRODUCTIVITY OF MSME EMPLOYEES BAKPIA ENY 523: A CASE STUDY OF WORK PRODUCTIVITY COUNSELING - Suripto, Suripto; Khoirudin, Rifki; Adi Kurniawan , Mahrus Lutfi; Safar Nasir, Muhammad; Salim, Agus (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Counseling to increase productivity in MSMEs Bakpia Eny 523 Yogyakarta aims to increase understanding of the concept of work productivity, time management skills, and employee work motivation. Through training, it is hoped that employees can understand the importance of efficiency in the production process and good time management. The evaluation was carried out using a questionnaire based on the Likert scale to measure the level of understanding and intention of change in increasing productivity. The results show that an understanding of productivity, clear time management, and appreciation of employee contributions play an important role in increasing motivation and commitment to positive changes in the way of working. Most of the respondents felt motivated and committed to implementing more efficient work methods after participating in this counseling, focusing on improving product quality and optimal use of resources.